Formulation of Ethanol Extract Spray Gel Preparation of Sweet Starbumber Leaves (Averrhoa carambola L.) - Eka Ammyta Putri Perdanti; Gigih Kenanga Sari; Maulita Saraswati (Yayasan Citra Dharma Cindekia, 2023)
The sweet star fruit leaf plant (Averrhoa carambola L.) is a plant that has many benefits, one part of the plant that is often used is the leaves which contain alkaloids, flavonoids, saponins and tannins that can be made indo spray gel preparations. Spray gel or commonly called spray gel is a gel that has an aqueous phase of 10-90% of the weight of the spray preparation. This research aims to formulate a spray gel preparation of ethanol extract of sweet starfruit leaves (Averrhoa carambola L.) by testing the physical stability of the spray gel preparation. The formulation of spray gel preparations of sweet starfruit leaf extract (Averrhoa carambola L.) with concentrations of 0.1%, 1% and 1.5% was researched using laboratory experimental methods. Physical stability tests of spray gel preparations include organoleptic tests, pH tests, homogeneity tests, viscosity tests, spray pattern tests, dry time tests, cycling tests and centrifugation tests.The results of testing the physical stability of spray gel preparations for each formula fall within the range of requirements for spray gel preparations. To test the physical stability of the spray gel preparation after the cycling test, the viscosity test and pH test for each formula showed a decrease in each formula, while the organoleptic test did not show a significant change in each formula after the cycling test. The centrifugation test results for each formula showed that it was stable, indicated by the absence of syneresis or phase separation. Based on research, it was found that at the highest concentration the spray gel preparation of ethanol extract of sweet star fruit leaves (Averrhoa crambola L.) had a good physical stability test.